Hipnoterapi untuk penurunan berat badan pada individu obes - Hera Nurlita; Martalena Purba; Ira Paramastri (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2007)
Background: Obesity is a major health problem. There is a dramatic increase in the prevalence of obesity in many countries and in Indonesia. Evidence strongly suggests that dietary intake of high energy, high fatty foods and decrease physical activity are the primary causes of obesity. Obesity has been directly linked with mortality and morbidity from chronic diseases. Treatment for obese person involves multiple techniques and strategies including dietary therapy, physical activity, behavior therapy as well as combination of these strategies. Hypnosis enables someone to change habits, achieve goals to reduce weight and long-term weight loss maintenance.Objective: This study was conducted to know whether hypnosis have an effect for weight loss in obese people.Method: The study was a quasi-experimental with a pre and posttest control group design. Subjects were divided into two groups; 11 obese individuals received hypnotherapy and nutrition counseling and another 11 obese individuals received only nutrition counseling. Weight was measured at the beginning of the intervention and thereafter. Food intake was analyzed with computer software. Wilcoxon was used to analyze the data.Result: Results of study showed that weight reduction varied between case and control (with hypnotherapy and without hypnotherapy). The average weight loss among the two groups (3.29 kg in case and 0.60 kg in control) were significantly different (p<0.05). The average energy intake among the two groups (1278.4 kcal in case and 1659 kcal in control) were significantly different (p<0.05). Physical activity in case group was higher than the control group.Conclusion: A combination of hypnotherapy and nutrition counseling leads to a better weight reduction than the one without hypnotherapy.